The Overview of common ground in translation studies: definition, translation types, texts and meaning, and text types - Adriadi Novawan (Journal of English in Academic and Professional Communication, 2023)
In this globalized and digitalized world, translation activities play a crucial role in facilitating interlingual communication, opening access to knowledge and information worldwide, and strengthening cultural exchange across the globe. This paper discusses the essential issues related to translation, translation types, texts and meaning, and the types of texts in translation. Each part explores translation theories from pioneers of translation theories such as Jakobson, Catford, Nida and Taber, Newmark, and Larson, while modern theories such as Munday and others are also elaborated to provide a common ground for translation practice.